The influence of system interactivity and technical support on learning management system utilization - Zadeh, Sousan Baleghi; Mohd Ayub, Ahmad Fauzi; Mahmud, Rosnaini; Mohd Daud, Shaffe (Laboratory of Knowledge Management & E-Learning, Faculty of Education, The University of Hong Kong, 2017)
In recent years, there has been a growing increase in using Learning Management System (LMS) by universities. However, its utilization by students is limited in Malaysia. The main purpose of the present study is to develop and test a model that predicts LMS utilization by Malaysian higher education students. Based on the Technology Acceptance Model, the study investigated the relationships among six constructs (system interactivity, technical support, perceived ease of use, perceived usefulness, behavioral intention to use and LMS use) through structural equation modelling. The participants were 216 undergraduate students from a local university in Malaysia. The result of the study revealed that system interactivity had a significant effect on perceived usefulness, but not on perceived ease of use; technical support had a significant effect on perceived ease of use, but not on perceived usefulness.